Don't look back - Hurwitz, Gregg Andrew (St. Martin's Press, 2014)
In Don't Look Back, Eve Hardaway, newly single mother of one, is on a trip she's long dreamed of--a rafting and hiking tour through the jungles and mountains of Oaxaca, in southern Mexico. Eve wanders off the trail, to a house in the distance with a menacing man in the yard beyond it, throwing machetes at a human-shaped target. Disturbed by the sight, Eve moves quickly and quietly back to her group, taking care to avoid being seen. As she creeps along, she finds a broken digital camera, marked with the name Teresa Hamilton. Later that night, in a rarely used tourist cabin, she finds a discarded prescription bottle--also with the name Teresa Hamilton. From the camera's memory card, Eve discovers Teresa Hamilton took a photo of that same menacing looking man in the woods. Teresa Hamilton has since disappeared. Now the man in the woods is after whoever was snooping around his house. With a violent past and deadly mission, he will do anything to avoid being discovered. A major storm wipes out the roads and all communication with the outside world. Now the tour group is trapped in the jungle with a dangerous predator with a secret to protect. With her only resource her determination to live, Eve must fight a dangerous foe and survive against incredible odds--if she's to make it back home alive.--Publisher's description.